PENGARUH MODEL PEMBELAJARAN TEAM GAME TOURNAMENT TERHADAP HASIL BELAJAR SISWA SMP NEGERI 1 KRIAN - Delviana, Olivia Nathania; Indayati, Tatik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to describe the effect of the TGT (Team Game Tournament) type of cooperative learning model on the learning outcomes of class IX students in the natural sciences subject on the inheritance of living things in SMP Negeri 1 Krian. The research conducted was a quantitative research type of quasi-experimental design with a post-test only control group design. The data collection technique in this study was a test while the data analysis technique used a prerequisite test, namely the normality and homogeneity tests, the data obtained were normally distributed and homogeneous. Test the hypothesis using the independent sample t test from the posttest results of student learning outcomes in the experimental class and control class tested statistically showing a significance value of 0.000 0.05, which means that there is a significant influence from the application of the TGT (Team Game Tournament) cooperative learning modelon student learning outcomes on the inheritance of traits in living things at SMP Negeri 1 Krian.